2020
DOI: 10.1038/s41598-020-59265-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature fluctuations on spatial-temporal transmission of hand, foot, and mouth disease

Abstract: Hand, foot, and mouth disease (HFMD), predominantly occurs among infants and children. Previous studies have shown that suitable, stable temperatures favor HFMD virus reproduction; however, temperature fluctuations also affect virus transmission, and there are, so far, no studies concerning the association between such fluctuations and the incidence of HFMD. The objective of this study was to map the spatial-temporal distribution of HFMD incidence and quantify the long-term effects of temperature fluctuations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
(50 reference statements)
3
2
0
Order By: Relevance
“…As shown in this study, other countries in Asia, such as China 29 , Singapore, and Japan 7 , also observed an increment of more than two-fold in the number of cases throughout the last decade. Besides, this study also found that areas with high population density and more developed economies, such as Kota Kinabalu and Penampang had high number of HFMD cases, which is consistent with previous studies 30 . This may be attributed to the economic development and urbanization in these areas leading to more frequent communication and close contact with individuals, resulting in a higher risk of HFMD transmission 31 .…”
Section: Discussionsupporting
confidence: 92%
“…As shown in this study, other countries in Asia, such as China 29 , Singapore, and Japan 7 , also observed an increment of more than two-fold in the number of cases throughout the last decade. Besides, this study also found that areas with high population density and more developed economies, such as Kota Kinabalu and Penampang had high number of HFMD cases, which is consistent with previous studies 30 . This may be attributed to the economic development and urbanization in these areas leading to more frequent communication and close contact with individuals, resulting in a higher risk of HFMD transmission 31 .…”
Section: Discussionsupporting
confidence: 92%
“…Using the time series data of HFMD incidence in 31 provinces in China from 2008 to 2017, this study con rmed the correlation between temperature and hand, foot and mouth disease incidence, which is consistent with the previous research results (Xu et al, 2020;Pearson et al, 2020). However, different from other studies, we found that there are threshold differences in the impact of temperature on the incidence of HFMD in different regions and age groups, which can be used as a reference for early warning and guide the public health protection of HFMD.…”
Section: Discussionsupporting
confidence: 90%
“…In terms of the influence of meteorological fluctuations, the facilitating effect of the increase in temperature on the risk of HFMD is found more significant in the 3-year period, while the inhibitory effect of the increase in precipitation is more obvious in the 5-year period. A previous study in North China pointed out that large fluctuations in environmental conditions may prevent the reproduction and transmission of enteroviruses ( Xu et al., 2020 ), and our results proved this conclusion by focusing on the impact of temperature and precipitation fluctuations on HFMD.…”
Section: Discussionsupporting
confidence: 85%